Co-combustion of municipal solid waste and hydrochars under non-isothermal conditions: Thermal behaviors, gaseous emissions and kinetic analyses by TGA–FTIR. (15th February 2023) - Zhang, Xuefei; Li, Yongling; Zhang, Xianwen; Ma, Peiyong; Xing, Xianjun
Abstract: Co-combustion of municipal solid waste (MSW) with hydrochars was proposed as an effective way for both simultaneous treatments of MSW with biomass and energy recovery. In this work, thermogravimetric analyzer coupled with Fourier transform infrared spectrometer was employed to study the (co-)combustion, gaseous emissions and combustion kinetics characteristics of MSW, hydrochars and their blends. The addition of hydrochars to MSW leads to lower burnout temperatures and the shorter combustion time. Hydrochar prepared at 200 °C (SD200) has a better co-combustion performance than hydrochars prepared at 230 (SD230) and 260 °C (SD260) in term of ignition, burnout and comprehensive combustion characteristic index, hydrochar prepared at 260 °C has a better co-combustion evenness. The addition of hydrochar to MSW changed the gaseous products emission patterns of MSW and reduced the release of CO, HCN, NO and HCl. Kissinger-Akahira-Sunose (KAS) and Flynn–Wall–Ozawa (FWO) methods were used to estimate the activation energy of MSW, SD200 and their blends, the minimum average activation energy was observed when the SD200 blending ratio was 70%, which was 75.65 kJ mol −1 by KAS and 82.12 kJ mol −1 by FWO, respectively. Graphical abstract: Image 1 Highlights: Co-combustion of MSW with sawdust hydrochars were studied by TG-FTIR. The combustion characteristics of MSW could be improved by blending hydrochar. Hydrochar prepared at 200 °C has the best co-combustion performance with MSW. Hydrochar help reduce the release of CO, HCN, NO and HCl during MSW combustion. The lowest E a was obtained when the hydrochar mass blending ratio was 70%.